Separase activity distribution can be a marker of major molecular response and proliferation of CD34+ cells in TKI-treated chronic myeloid leukemia patients - Spiess, Birgit; Kleiner, Helga; Flach, Johanna; Fabarius, Alice; Saußele, Susanne; Hofmann, Wolf-Karsten; Seifarth, Wolfgang (Annals of hematology, 2020)
Separase, a cysteine endopeptidase, is a key player in mitotic sister chromatid separation, replication fork dynamics, and DNA repair. Aberrant expression and/or altered separase proteolytic activity are associated with aneuploidy, tumorigenesis, and disease progression. Since genomic instability and clonal evolution are hallmarks of progressing chronic myeloid leukemia (CML), we have comparatively examined separase proteolytic activity in TKI-treated chronic phase CML. Separase proteolytic activity was analyzed on single cell level in 88 clinical samples and in 14 healthy controls by a flow cytometric assay. In parallel, BCR-ABL1 gene expression and replication fork velocity were measured by qRT-PCR and DNA fiber assays, respectively. The separase activity distribution (SAD) value indicating the occurrence of MNCs with elevated separase proteolytic activity within samples was found to positively correlate with BCR-ABL1 gene expression levels and loss of MMR (relapse) throughout routine BCR-ABL1 monitoring. Analyses of CD34+ cells and MNCs fractionized by flow cytometric cell sorting according to their separase activity levels (H- and L-fractions) revealed that CD34+ cells with elevated separase activity levels (H-fractions) displayed enhanced proliferation/viability when compared with cells with regular (L-fraction) separase activity (mean 3.3-fold, p = 0.0011). BCR-ABL1 gene expression positivity prevailed in MNC H-fractions over L-fractions (42% vs. 8%, respectively). Moreover, expanding CD34+ cells of H-fractions showed decreased replication fork velocity compared with cells of L-fractions (p < 0.0001). Our data suggests an association between high separase activity, residual BCR-ABL1 gene expression, and enhanced proliferative capacity in hematopoietic cells within the leukemic niche of TKI-treated chronic phase CML.
Im Titel ist "+" hochgestellt
Gesehen am 07.12.2021